(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The study aimed to find out the effectiveness of using the Jigsaw strategy in the achievement of mathematics among the first intermediate grade students. To achieve the objectives of the study, the semi-experimental approach was used. Based on the results of two control and experimental groups; They were chosen randomly from the first intermediate grade students, where the researcher prepared study tools and materials, which are: an achievement test (prepared by the researcher), in addition to the teacher’s guide (prepared by the researcher) and after verifying the validity and reliability of the study tools and materials, they were applied to the study sample and its strength ( 80) female students were divided into two groups; The experimental group consisted of (40) students who studied using the Jigsaw strategy, and the control group consisted of (40) students who studied using the traditional method. Statistically significant differences at the significance level (α = 0.05) between the mean scores of the experimental group and the control group in the post-academic achievement test in favor of the experimental group due to the use of the Jigsaw strategy.Introductory words: effectiveness, Jigsaw strategy, achievement, mathematics, intermediate first grade.